Controle jurídico de resultado das políticas públicas a partir da análise comportamental e econômica do direito: estudo das contingências que envolvem a judicialização da política pública de assistência farmacêutica e impactam a sua eficácia, efetividade e eficiência - Haber, Melina Tostes (2018)
This paper focus in studying public policies, specially, on how to control its implementation, so the most results and social success can be achieved. Initially it will be revised the legal doctrine regarding public policies and its necessity to be in constant evaluation, in order to truly operates its pretended effects on society. In order to achieve that, the law should be able to dialogue with social facts. This article proposes that physiological theories, such as behaviorism, can contributed to define concepts like efficacy and effectiveness of public policies. In addition, it will also debate how law and economics and its concepts of efficiency, can be applied to public policies. In conclusion, it will be demonstrated how this can be put in practice, using as an example the innumerous judicial cases in which the people demands medication towards the government.